FEATURES OF IMMUNOLOGICAL BLOOD MARKERS IN PREMATURE NEWBORNS - Ш. Мухамедова; Ш. Ганієва; Б. Рустамов; З. Муртазаєва (Неонатологія, хірургія та перинатальна медицина, 2025)
Premature birth remains a global healthcare issue due to ongoing challenges in prediction and prevention. Current predictors are limited by low effectiveness, the need for invasive sampling, and the inability to identify at-risk patients in a timely manner to ensure effective intervention. Multiple etiologies of preterm birth often involve an inflammatory component. Therefore, a deeper understanding of the inflammatory mechanisms involved in preterm birth may provide opportunities for identifying new predictors of preterm labor.